Implementasi Fuzzy Logic untuk Kontrol Gerak Tari pada Robot Humanoid dengan Menerapkan Sensor Deteksi Warna TCS3200 - Dessy Ana Sari; Elfira Makmur; Retyana Wahrini (Prodi Teknik Elektro Universitas PGRI Banyuwangi, 2023)
One of the prominent competitions in the national robot series, the Indonesian dancing Robot Contest (KRSTI), assesses the dependability of various dancing robots by having them perform traditional dances from Indonesia. In this study, the authors use fuzzy logic to control the mobility of the dancing robot by determining whether it poses and dances in accordance with the KRI dance zone based on the input produced by the TCS3200 color sensor. In order to create a robot that may move in accordance with its designated zone, the Mamdani fuzzy approach, which employs the IF-ELSE principle, is used for decision-making.